Avaliação clínica, laboratorial e histopatológica do efeito de drogas imunossupressoras na reativação da toxoplasmose crônica em modelo murino com a cepa ME 49 no camundongo BALB/c - Alves, Fabiana Santiago Aleixo (2008)
This work was evaluated for the potential reactivation of Toxoplasmosis in murine model similar to human immunosuppression being developed in BALB/c mice, which were 40 days infected with 20 cysts of ME 49 strain of Toxoplasma gondii and after 60 days was initiated treatment with immunosuppressant drugs, Azathioprine in dosage of 10mg/kg five times a week in days, Dexametasone in dosage 2.5mg/kg per day per mouse, three times per week on alternate days, Cortisone acetate in 50mg twice a week in subcutaneous injection of cortisone acetate alone, or associated with its proper controls. Treatment was continued for 28 days. The use of the Dexametasona or Azathioprine isolated or associated with, a factor not caused by reactivation of serological tests, clinical or histopathological but associated with cortisone acetate led to a clinical diagnostic framework of a voluntary recall because of injuries in epidermal 62.5% of the mice that lot compared to its proper controls, however mortality was not observed in any of the groups tested